Factors influencing fall prevention for patients with spinal cord injury from the perspectives of administrators in Canadian rehabilitation hospitals - H. Singh; B. C. Craven; H. M. Flett; C. Kerry; S. B. Jaglal; M. P. Silver; K. E. Musselman (BMC, 2019)
Abstract Background Fall prevention is a priority in Canadian tertiary rehabilitation hospitals. We aimed to understand the perspectives of hospital administrators on the challenges experienced when implementing fall prevention policies/procedures for patients with spinal cord injury (SCI) in tertiary rehabilitation hospitals. Methods Semi-structured interviews were conducted with 10 administrators employed in six Canadian tertiary rehabilitation hospitals. Guided by an interpretive description framework, interviews were analyzed using a constant comparison approach. Results Challenges with fall prevention experienced by administrators fell into the three categories: 1) fall prevention policy and procedural challenges (e.g. fall prevention policy not SCI-specific, expectation of zero falls, determining contributing factors, learning from falls, and overall effectiveness of the fall prevention policy), 2) clinician-related challenges (e.g. variable staff adherence with the organizations' fall prevention procedures, inconsistent delivery of fall prevention education, and integrating individualized fall risks to guide clinical practice), and 3) patient-related challenges (e.g. balancing risk vs independence and rehabilitation progress, responsibility for fall prevention, and non-preventable falls). Conclusions Fall prevention policies/procedures required by the hospitals were insufficient for clinical practice in SCI rehabilitation.